Human Robotics: Neuromechanics and Motor Control - Burdet (MIT Press, 2013)
Monograph
fulltext
Keywords: Bioengineering; Computing and Processing; Components, Circuits, Devices and Systems; Signal Processing and Analysis; Robotics and Control Systems